Current concepts and future directions in hip arthroscopy for femoroacetabular impingement: Techniques, challenges, and innovations - Sujeet Kumar Chaudhary; Binod; Vishal Kumar Singh; Manjul gupta (Journal of Orthopaedic Reports)
Background: Femoroacetabular impingement (FAI) is a pathological condition characterized by abnormal contact between the femoral head and acetabulum, leading to hip joint damage and early osteoarthritis, particularly in young adults. Hip arthroscopy has emerged as a preferred technique for the diagnosis and management of FAI due to its minimally invasive nature and favorable patient outcomes. Aim & Objective: This review explores current concepts in hip arthroscopy for FAI, analyzing surgical techniques, complications, patient-reported outcomes, and innovations. It further examines advancements like robotic-assisted surgery, advanced imaging technologies, and biologics which are shaping the future of hip arthroscopy in FAI management. Methods: A systematic review of the literature was conducted, incorporating data from 20 peer-reviewed articles published in the last 10 years. Studies focusing on surgical techniques, complications, patient-reported outcomes, and advancements in arthroscopic technology were analyzed. Results: Hip arthroscopy has shown promising results in improving pain and function in patients with FAI. However, complications such as chondral damage, labral re-tears, and heterotopic ossification remain challenges. Innovations like robotic assistance, advanced imaging, and biologics are enhancing precision and outcomes, contributing to improved patient care. Conclusion: Hip arthroscopy for FAI continues to evolve, offering improved outcomes through refined techniques and technological advancements. Future directions lie in personalized treatment approaches, enhanced imaging, and the integration of regenerative therapies to further optimize outcomes.